1992
DOI: 10.1002/pssa.2211330229
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lattice Site and Valence of Manganese in Polycrystalline BaTiO3, and n-BaTiO3, by Electron Paramagnetic Resonance

Abstract: The EPR spectra of manganese in polycrystalline BaTiO3 and n‐BaTiO3 (lanthanum‐doped BaTiO3) are studied. The measurements are carried out in all four phases of BaTiO3 to follow the phase transformations of the ceramic material by means of the microscopic probe manganese. The valence state of manganese in BaTiO3 and n‐BaTiO3 is determined and the site of incorporation is estimated from the experimental spin‐Hamiltonian parameters obtained in this study on the basis of the existing results of single crystal EPR. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
11
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 11 publications
8
11
1
Order By: Relevance
“…The signal near g = 2 was assigned to Fe 3+ ion [47,48]. The line with g > 2 was attributed to paramagnetic ions in sites of relatively strong crystal field [49]. The ESR spectra of Nd-Bi 2 O 3 (4f 3 with 4 I 9/2 ) show hyperfine structure [50].…”
Section: Esr Spectroscopymentioning
confidence: 99%
“…The signal near g = 2 was assigned to Fe 3+ ion [47,48]. The line with g > 2 was attributed to paramagnetic ions in sites of relatively strong crystal field [49]. The ESR spectra of Nd-Bi 2 O 3 (4f 3 with 4 I 9/2 ) show hyperfine structure [50].…”
Section: Esr Spectroscopymentioning
confidence: 99%
“…Previous EPR studies of bulk BaTiO 3 in the form of single Phase Transitions 767 crystals and ceramics have shown that the EPR spectra of the Mn 2C and Fe 3C impurity ions are strongly sensitive to crystal structure transformation in BaTiO 3 . [16,17] These paramagnetic ions were exploited in study of BaTiO 3 nanoparticles as well, but only at T > 296 K. [15,18,19] We used this opportunity to detect the orthorhombic-rhombohedral phase transition in nanoparticles and BTO@SiO 2 ceramics. Our samples were not specially doped by paramagnetic ions.…”
Section: Epr Datamentioning
confidence: 99%
“…Transition-metal (TM) ions doped into BaTiO 3 play an important role for photorefractivity to occur (7)(8)(9). Since useful information on valence state, substitutional site and defect structure of TM ions in crystals can be obtained by analyzing their EPR spectra, many EPR studies for TM ions in BaTiO 3 crystals have been made (9)(10)(11)(12)(13). Among them, the EPR spectra of 3d n TM ions in BaTiO 3 were widely studied.…”
Section: Introductionmentioning
confidence: 99%